The Implementation of Al-Ghazali's Concept of Adab Before Knowledge in the School Culture of SMP GPI Solokan Jeruk - Anggi Nurmalita; Tryana Hafilda; Adi Sukma Barkah; Muhammad Luthfi Dzulfikar; Nurhilal Ahmad Fathin; Hasan Basri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research is motivated by the critical importance of strengthening students' character and morality amidst modern moral challenges, where the aspect of adab (etiquette/morals) is often neglected in pursuit of purely academic achievements. Al-Ghazali's epistemological thought on the principle of